Padlet for Project-based Learning in an Entrepreneurship Course - Dency Flenny, Gawin (JCSHD, 2021)
Padlet is a collaborative online tool that is widely used to complement online learning. This study investigates students' perception of using Padlet while executing project-based learning activities in the learning of entrepreneurship content and skills. Participants were assigned to use Padlet tofacilitate remote group work discussions. Once the activities were completed, they filled out an online survey to capture their opinions and perceptions of the use of Padlet in their respective projects. The quantitative findings revealed that more than half of the participants agreed that Padlet is a useful online tool to support project-based learning activities. They also agreed Padlet can be used to nurture students’ soft skills. Less than half still wanted to use Padlet if their internet connections were reliable. However, the rest were unsure of continuing using Padlet, and they indicated a preference to use other online tools. A few factors were identified to have also influenced the correlation between Padlet usage and assignments. Based on qualitative findings, although Padlet was viewed as a great collaborative tool supporting project-based learning activities in entrepreneurship education, it must be used with other online tools to overcome its technical shortcomings. Hence, modifying pedagogical strategies shall also be considered for making students participate actively in online discussion. In future, an in-depth investigation should focus on understanding the effectiveness of Padlet in entrepreneurship education in post-pandemic scenarios.